Development of polycaprolactone biodegradable films reinforced with silver-doped organoclay and effect on the microbiological quality of ground beef meat - Ilaslan, Kerem; Tornuk, Fatih; Durak, M. Zeki (WILEY, 2022)
In this work, a comparative study was held to obtain biodegradable antibacterial nanocomposite films using polycaprolactone (PCL) and silver-ion-doped organomodified halloysite (HNT) and montmorillonite (MMT) nanoclays. The PCL-based nanocomposite films (PNFs) were characterized in terms of thickness, mechanical, thermal, morphological, molecular, color, gas barrier, and antibacterial activity properties. The PNFs were also tested for enhancement of microbiological quality of ground beef. The addition of the Ag-doped nanoclays provided improved mechanical (tensile strength [TS] and elongation at break [EB]) and barrier (water vapor and oxygen permeability) properties in comparison to the pure PCL film. PNF formation increased the crystallization temperature (T-c) of pure PCL by about 1 degrees C and decreased the crystallinity (X-c) from 44.8% to 41.3%. The PNFs exhibited strong in vitro antibacterial activity against the test pathogens and bacteriostatic effect on natural bacterial load of ground beef meat during the storage, thus providing it better microbiological quality. Novelty impact statement This work focuses on the production and characterization of new packaging materials reinforced with silver-ion-doped halloysite and montmorillonite nanoclays and improving the microbial quality of ground beef meat by this material. PCL-based nanocomposite films reinforced with Ag-doped nanoclays had enhanced mechanical and barrier properties and gained in vitro antibacterial activity. Additionally, its antibacterial potential in food applications was demonstrated by the ground beef meat packaging studies.
Keywords: NANOCOMPOSITE FILMS; PACKAGING MATERIALS; BARRIER PROPERTIES; COMPOSITE FILMS; RAPID DETECTION; ESSENTIAL OIL; EDIBLE FILM; MONTMORILLONITE; CLAY; GAS; Food Science & Technology